(untitled) (SAARC Journal of Agriculture, 2014)
A field experiment was conducted to find out the effect of different integrated disease management (IDM) packages on severity of basal rot (Fusarium oxysporum), white rot (Sclerotium rolfsii) and stemphylium blight (S. vesicarium) diseases, and bulb yield of onion (Allium cepa L.) variety Agrifound Light Red. Nine IDM packages consisting of NPK fertilizers, farm yard manure, biocontrol agents and spray of fungicides starting from 30 days of transplanting at 15 days interval were applied. The incidence of basal rot and white rot of onion bulbs ranged from 0.98- 4.31% and 0.00-0.96%, respectively. The highest incidence of basal rot (4.31%) and white rot (0.96) was recorded in bulbs harvested from untreated control. The lowest incidence of basal rot (0.98%) was found in bulbs harvested from the IDM package consisting of NPK @ 100:50:50 kg ha-1 + FYM @ 10 t ha-1 + vermicompost @ 1 t ha-1 + Ps. fluorescens @ 5 kg ha-1 + copper oxychloride @ 0.3%). White rot did not appear under this package. The lowest Stemphylium blight intensity (3.87%) was achieved with the package having four foliar sprays of propiconazole @ 0.1% followed by mancozeb @ 0.25% and copper oxychloride @ 0.3%. The IDM package increased the bulbs yield over standard check by 25.54% and over untreated control by 109.42%. The average highest bulb diameter (54.15 mm) and bulb size index (23.27 cm2) and lowest incidence (0.98%) of basal rot disease in onion bulbs was also obtained with IDM package consisting of NPK @ 100:50:50 kg ha-1 + FYM @ 10 t ha-1 + vermicompost @ 1 t ha-1 + Ps. fluorescens @ 5 kg ha-1 + copper oxychloride @ 0.3%). DOI: http://dx.doi.org/10.3329/sja.v11i2.18401 SAARC J. Agri., 11(2): 49-59 (2013)